
See question detail
Because the tank doubles everr minute, the tank is half full in 9 minutes.

See question detail
Note that from \(3^x=\left(5^w+2^y\right)\left(5^w2^y\right)\) we can infer \(5^w+2^y=3^x,5^w2^y=1\) because if \(5^x+2^y=3^m,5^x2^y=3^{xm}\) then \(\left(5^w+2^y\right)+\left(5^w2^y\right)=2.5^w=3^m+3^{xm}⋮3\) (a contradiction)

See question detail
We will show there is exactly one set of solution, namely x = y = z = 2. To simplify the equation, we consider modulo 3. We have:
\(1=0+1^y\equiv3^x+4^y=5^z\equiv\left(1\right)^z\left(mod3\right)\)
It follows that \(z\) must be even, say z = 2w, then:
\(3^x=5^z4^y=5^{2w}2^{2y}=\left(5^w+2^y\right)\left(5^w2^y\right)\)
\(\Rightarrow\left\{{}\begin{matrix}5^w+2^y=3^x\\5^w2^y=1\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}\left(1\right)^w+\left(1\right)^y\equiv0\left(mod3\right)\\\left(1\right)^w\left(1\right)^y\equiv1\left(mod3\right)\end{matrix}\right.\)
=> \(w\) is odd and \(y\) is even. If \(y>2\) then \(5\equiv5^w+2^y=3^x\equiv1\)or \(3\) (mod 8), a contradiction. So \(y=2\). Then \(5^w2^y=1\) => \(w=1,z=2\) and finally \(x=2\).

See question detail
We have:
\(\left(x+y+z\right)^3\left(x^3+y^3+z^3\right)=3\left(x+y\right)\left(y+z\right)\left(z+x\right)\)
\(\Rightarrow8=\left(3z\right)\left(3x\right)\left(3y\right)\) (1)
Since \(\left(3x\right)+\left(3y\right)+\left(3z\right)=9\left(x+y+z\right)=93=6\) (2)
From (1) and (2) we infer \(\left(x,y,z\right)\) would be (1,1,1), (5,4,4), (4,5,4), (4,4,5).

See question detail
Without loss of generality, we may assume gcd(a,b,c) = 1.
(otherwise, if d=gcd(a,b,c) the for a'=a/d, b'=b/d, c'=c/d, the equation still holds for a', b', c' and a'b'c' is still a cube if only if abc is a cube).
We multiply equation by abc, we have:
\(a^2c+b^2a+c^2b=3abc\)(*)
if \(abc=\pm1\), the problem is solved.
Otherwise, let p be a prime divisor of abc. Since gcd(a,b,c)=1, the (*) implies that p divides exactly two of a, b,c. By symetry, we may assume p divides a, b but not c. Suppose that the lagest powers of p dividing a, b are m, n, respecively.
If n < 2m, then \(n+1\le2m\) and \(p^{n+1}\) \(a^2c,b^2c,3abc\). Hence \(p^{n+1}\)\(c^2b\), forcing \(\)\(p\)\(c\) (a contradiction). If n > 2m, then \(n\ge2m+1\) and \(p^{2m+1}\)\(c^2b,b^2a,3abc\). Hence \(p^{2m+1}\)\(a^2c\), forcing \(p\)\(c\) (a contradicton). Therefore n = 2m and \(abc=\Pi p^{3m}\), \(p\)\(abc\), is a cube.

See question detail
Since \(3^{\dfrac{1}{3}}>4^{\dfrac{1}{4}}>5^{\dfrac{1}{5}}>...\) we have \(y^z\ge z^y\) if \(y\ge3\).
Since \(1\le x\le y\), the only possible values for (x, y) are (1,1), (1,2), (2,2). These lead to the equations \(1+1=z,1+2^x=z,4+2^z=z^2\).
The firt equation has the unique solution (1,1,2).
The second equarion has no solution because \(2^x>z\).
The third equation has also no solution since \(2^x\ge z^2,z\ge4\) and (2,2,3) is not a solution.
So the equation has unique solution (1,1,2).

See question detail
a) In quadrilateral DAMB: \(\angle A+\angle D+\angle B+\angle MAB=360^o\) (1)
In triangle MEC: \(\angle E+\angle C+\angle MEC=180^o\) (2)
Sum (1) and (2): \(\angle A+\angle B+\angle C+\angle D+\angle E+\angle MAB+\angle MEC=540^o\)
Since \(\angle MEC=\angle MAB\)
We have: \(\angle A+\angle B+\angle C+\angle D+\angle E+360^o=540^o\)
\(\Rightarrow\angle A+\angle B+\angle C+\angle D+\angle E=540^o360^o=180^o\)
b) if 2A=B=C=D=E we infer A = 20^{o}

See question detail
Let \(Q\left(x\right)=\left(x+1\right)P\left(x\right)x\), (*)
since \(P\left(n\right)=\dfrac{n}{n+1}\) we infer:
\(Q\left(n\right)=\left(n+1\right)P\left(n\right)n=0\) for \(n=0,1,..,2015\).
Because P is a polynomial of dgree 2016, Q is a polynomial of dgree 2016. Q has 2016 solutions (0, 1, .. , 2015) so Q can be expressed in a form:
\(Q\left(x\right)=a\left(x0\right)\left(x1\right)...\left(x2015\right)\) (**)
In other hand, in (*) we set x = 1 then \(Q\left(1\right)=1\). And replace to (**) we have:
\(1=Q\left(1\right)=a\left(1\right)\left(2\right)...\left(2016\right)\)
\(\Rightarrow a=\dfrac{1}{2016!}\)
Finally \(Q\left(x\right)=\dfrac{1}{2016!}\left(x0\right)\left(x1\right)...\left(x2015\right)\)
\(\Rightarrow Q\left(2016\right)=\dfrac{1}{2016!}2016.2015...1=1\)
from (*) \(Q\left(2016\right)=\left(2016+1\right)P\left(2016\right)2016\)
\(\Rightarrow\left(2016+1\right)P\left(2016\right)2016=1\)
\(\Rightarrow P\left(2016\right)=\dfrac{2017}{2017}=1\)
 View more →

Continuing the previous post:
Question by John  Discuss with MathYouLike
I have another problem: Calculate the area of the curved square below (crossed area):
 View more →